Nilai-nilai Kearifan Lokal Masyarakat Gayo dalam Perspektif Ekonomi Syariah - Linge, Abdiansyah (Lembaga Yasin AlSys, 2022)
Entrepreneurship concepts or values based on local wisdom of the Gayo people are the foundation of the behavior of the Gayo community in economic activities, so that sharia entrepreneurial values can be built that originate from the smallest community behavior patterns, namely culture, and can be a driving force for community interest in carrying out economic activities of production and distribution with the value of entrepreneurship. This study uses a micro-ethnographic approach by developing indigenous Gayo linguistics as a concept of sharia entrepreneurship. The integration of spiritual values, planning, sustainability of economic and moral resources is the concept of sharia entrepreneurship in Gayo customary local wisdom.